Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

Reactive organic matter destabilizes Fe-mediated phosphorus retention through Fe–S–P decoupling in lake sediments - Yaping Liu; Lixin Jiao; Jia He; Liansheng He; Di Song; Jing Liu; Yaru Feng (Water Research, 2026)

Tailoring MOF/PEO interface via self-assembled deep eutectic layer for advanced solid polymer electrolyte - Jing Li; Yifan Huang; Yaping Sun; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Augmented innate and humoral immune responses enhance early and durable rabies protection by a CD40L-overexpressing rabies vaccine - Xiao Xing; Yufang Wang; Zhimin Xiong; Die Liu; Yong Wang; Yang Hu; Yaping Liu; Yingying Li (Veterinary Microbiology, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Conserved and specific roles of photoperiod and circadian rhythm-related genes on flowering time in Lotus japonicus - Wang Yihan; Dai Xinglong; Liu Jiao; Liu Yujuan; Chen Siping; He Yijun; Chen Chen; Jiang Huawu; Kong Fanjiang; Chen Yaping (Plant Science, 2026)

Integrated prediction of rainfall-induced landslides using zone parameterization and physical-based probabilistic modelling - Renwen Liu; Wei Zhou; Yaping Zhou; Huaqiang Yin; Ming Chen (Geomorphology, 2026)

Next-generation intelligent prepared aquatic dishes: research progress in digital heat control and quality evaluation empowered by industry 4.0 - Ying Xie; Min Zhang; Qi Yu; Yaping Liu (Food Research International, 2026)

Anomalous thermally enhanced output and ion-exchange repairability of flame-retardant waste cotton textile-based triboelectric nanogenerators - Kun Zhao; Yaping Liu; Li Chen; Mengdan Shen; Xuefeng Lu; Yuandong Li; Yong Wang; Kewei Zhang (Chemical Engineering Journal, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Controlled biosynthesis of curdlan oligosaccharides with tunable degree of polymerization and their prebiotic effects on gut microbiota - Yaping Pan; Yuying Wang; Zhilei Liu; Tong Liang; Zepeng Chang; Qingyu Wang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Bioresource Technology, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Combined CO₂ and topographic uplift forcing on vegetation and climate change in the North China Plain since ∼6.5 Ma - Wei Liu; Likang Wang; Zhenjing Yang; Dianbao Chen; Dexuan Chen; Yaping Li; Xiaozhong Huang; Yunfa Miao; Baotian Pan (Global and Planetary Change, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Rapid particulate microplastics removal from stormwater: Distinct adsorption behavior and data-driven intelligent prediction - Yan Yaping; Song Xichen; Wang Xiaojuan; Liu Xiuyun; Zhou Jianqiang; Wang Gang; Zhang Tingting; Wei Bigui; Zhao Yaqian (Chemical Engineering Journal, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Prognostic factors and predictive modeling of in-hospital mortality among MDRO-positive inpatients: a retrospective cohort and GBD MICROBE study - Fan Jiang; Jian Li; Yahan Li; Yaping Yao; Ke Liu; Wei Dai; Hui Du (Antonie van Leeuwenhoek, 2026)

Retrieval of a desert steppe degradation index from hyperspectral data using self-supervised spectral representation learning - Liang Wang; Wenxia Zhang; Haichao Wang; Yufei Gao; Yuqi Liu; Qian Wang; Yaping Wang; Jianjun Li (Remote Sensing Applications: Society and Environment, 2026)

Bifurcation and phase desynchronization of vortex-induced vibration in a cable–buoy system under wave-induced parametric excitation - Yaobing Zhao; Yaping Liu; Qiang Wen; Qiufu Xie; Lincong Chen (Ocean Engineering, 2026)

Regulation of pH-responsive behavior in electrospun (copper sodium chlorophyllin-alizarin)/fish skin gelatin nanofiber-based hydrogel membranes and their application in real-time intelligent monitoring of fresh shrimp freshness - Botian Zhu; Junru Wang; Hualin Zhang; Haoyou Jiang; Mengmeng Zhao; Yeheng Cao; Yaping Huang; Xuyang Feng; Shuhao Min; Zheng Liu; Ying Wang (Food Bioscience, 2026)

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

Promoting high energy density Mn-based layered oxide cathodes via surface structural regulation for sodium-ion batteries - Maohan Liu; Lingyi Kong; Xinyu Zhang; Yaping Yan; Haiyan Hu; Hanshen Xin; Jiayang Li; Yubin Niu; Yanfang Zhu; Yao Xiao (Chemical Engineering Journal, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

Enhancing the leaching of copper oxide ores with high contents of calcium-magnesium alkaline bearing gangue by carboxymethyl chitosan - Jinrui Zhou; Wei Guo; Siqi Yang; Xianping Luo; Louyan Shen; Zhiyong Gao; Hongbo Zhao; Yaping Liu (Minerals Engineering, 2026)

Efficient green view index quantification from LiDAR point clouds - Hua Yeyu; Qian Yuguo; Wang Jianhai; Liu Yaping; Zhou Weiqi (Landscape and Urban Planning, 2026)

Fluid–structure interaction training of integral conservation physics-informed neural networks for blood flow in elastic vessels - Youqiong Liu; Li Cai; Yaping Chen; Qingsheng Liu (Computer Physics Communications, 2026)

High porosity poly(porous liquid)s based on multiple hydrogen bonds for rapid ammonia response - Yisong Liu; Jing Zhang; Shizhang Li; Fangfang Su; Yangyang Xin; Yating Zhang; Jinliang Xie; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Dynamics of positive leader branching in long air gaps: A statistical exploration - Lili Guo; Xiangen Zhao; Xiankang Wang; Xiaopeng Liu; Yao Yao; Yaping Du; Junjia He (Atmospheric Research, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Dynamic changes in rainfall thresholds for post-seismic debris flows using logistic regression and resampling - Renwen Liu; Wei Zhou; Huaqiang Yin; Yaping Zhou; Ming Chen (Bulletin of Engineering Geology and the Environment, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

BAMBI modulates proliferation, apoptosis, and hormone secretion in Jinding duck granulosa cells - Li Li; Xiaopan Liu; Changtao Liu; Chengfu Pan; Linli Zhang; Qingwu Xin; Zhongwei Miao; Liang Huang; Yuwei Li; Yaping Zhang; Qinlou Huang; Nenzhu Zheng; et al. (Animal Reproduction Science, 2026)

Chemically converted volume-resilience interface enables high-capacity zinc anode - Mingzhu Li; Xinyue Dou; Zhexuan Liu; Yaping Wang; Shuquan Liang; Guozhao Fang (Science Bulletin, 2026)

Elevated oxygen partial pressure reduces population exposure to hypoxia over the Qinghai–Xizang Plateau - Yanqiang Chen; Ying Zhang; Yaping Wang; Qinmei Han; Gangfeng Zhang; Xiaoyue Liu; Peijun Shi; Cunrui Huang (Science Bulletin, 2026)

Natural anti-tobacco mosaic virus constituents from plants: A review - Junmei Wang; Juxiang Wang; Shanshan Xiao; Yingshun Miao; Zhengxuan Wang; Jueting Liu; Hongwei Wang; Yaping Liu; Hesham R. El-Seedi; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

Occurrence of mycotoxins contamination in commercial feline and canine foods from China - Yaping Guo; Wei An; Xiumin Wang; Bing Han; Hui Tao; Bianfang Liu; Zhenlong Wang; Jinquan Wang (Mycotoxin Research, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

HSF-1 Regulates Autophagy to Govern Motor Function and Facilitate Toxic Protein Clearance in a C. elegans Model of Amyotrophic Lateral Sclerosis - Hui Xu; Yaping Shao; Jun Zhang; Yang Ni; Guowang Xu; Cong Liu; Yi Liang; Weidong Le (Neuroscience Bulletin, 2026)

Corrigendum to ‘Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis’ [Aquaculture 578 (2024) 740142] - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Reconstructing all-weather remotely sensed air temperature via a kernel-based temporal filling and bias correction (KTF-BC) framework - Yan Xin; Yongming Xu; Xudong Tong; Meng Ji; Yaping Mo; Yonghong Liu; Shanyou Zhu (Remote Sensing of Environment, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Multi-objective Optimization of Sponge City Storage Tank Considering Inlet and Outlet Water Conditions-based on NSGA-II Algorithm - Wang Xiaojuan; Ma Yingqiang; Li Hao; Qin Jie; Xiao Yifei; Yan Yaping; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Water Resources Management, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

A quantitative method of feeding demand for M. salmoides based on multi-source information fusion - Yaping Li; Hequn Tan; Yiren Zhang; Xuefei Liu (Biosystems Engineering, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Hydrogen bonding network induced by ambipolar small molecules facilitates high-performance all-solid-state Li batteries - Jing Li; Ruiqi Chai; Yaping Sun; Hengyi Wang; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Hierarchical PBO/Mica/MOF-303 composite films for tri-functional triboelectric nanogenerators: Enhanced charge density, flame retardancy, and humidity resistance - Yaping Liu; Mengdan Shen; Yuan Ye; Chaohui Zhang; Li Chen; Kun Zhao (Chemical Engineering Journal, 2026)

Emerging graphitic carbon nitride-based piezocatalysts for multifunctional applications: Environmental remediation, renewable energy and antibacterial technology - Yaping Gan; Shuqi Li; Khan Khalid; Gebrehiwot Gebreslassie; Mengru Li; Abera Beyene Gebresilassie; Xuezhi Liu; Lianjun He; Bin Lin (Chemical Engineering Journal, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Composition, Distribution and Constraining Factors of Fe Isotope (δ56Fe) in the Surface Soils of the Tibetan Plateau - Ting Wei; Zhiwen Dong; Eric Parteli; Xiaoli Liu; Shichang Kang; Yaping Shao (Journal of Earth Science, 2026)

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Zn isotopic composition and variability in large-scale aquatic environment of the Tibetan Plateau: implications for Zn migration and sources - Xiaoli Liu; Zhiwen Dong; Yan Yan; Rui Wu; Lunche Wang; Yaping Shao (Journal of Hydrology, 2026)

Effect of free fatty acids with different chain lengths and unsaturation degrees on hazardous compounds in canola oil cooking fumes - Yaping Lv; Zhan Ye; Zuqing Zhang; Yuanfa Liu (Food Chemistry, 2026)

Grass carp (Ctenopharyngodon idella) Kat5 mediates P53 acetylation to induce apoptosis and promotes GCRV replication - Bao Liu; Chuxin Wu; Xianggao Meng; Tingting Yu; Xucheng Zhang; Jing Liu; Mingzhi Li; Yaping Weng; Huiling Mao; Chengyu Hu; Lingbao Kong; Meifeng Li (Fish & Shellfish Immunology, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

An Advanced Fluorescent Molecularly Imprinted Sensor Based on Carbon Quantum Dots for Highly Sensitive Detection of 6-Mercaptopurine - Yinuo Liu; Zhengyuan Dai; Ying Wang; Shanshan Fu; Li Li; Yaping Ding (Journal of Fluorescence, 2025)

Effect of PEDV infection on IPEC-J2 cells on miR-328–3p/FoxO4/NF-κB/MLCK signaling axis - Yiming Wei; Zixuan Qi; Yaping Shuai; Shihui Zhao; An Liu; Jiuyuan Liu; Di Bao; Han Zhao; Shuang Zhang; Hongze Shao; Shushuai Yi; Jiangting Niu; et al. (Veterinary Microbiology, 2025)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

BFlow and Eckhardt methods perform best among non-tracer-based baseflow separation methods - Qiaoqiao Wang; Qiang Li; Yanli Qin; Xuanjiao Chai; Hongli Chen; Yaping Wang; Mingfang Zhang; Dengfeng Liu (Journal of Hydrology, 2025)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

Complete loss of 5-methyltetrahydrofolate in wheat during simulated gastric digestion - Fengyuan Liu; Jinxian Zheng; Yunfei Mo; Yaping Xiao; Yun Wang; Hua Zhang; Jing-Kun Yan; Yaqing Liu (Food Chemistry, 2025)

Heteroprotein complex co-aggregation of ovalbumin and ovotransferrin: structure formation and thermodynamics - Yaping Liu; Chenxin Huang; Jiajie Wang; Xianchao Feng; Meihu Ma (Food Hydrocolloids, 2025)

Elucidation of antibacterial efficacy and mechanism of the extract from fruit of Phyllanthus emblica L. against Vibrio cholerae and Staphylococcus aureus - Fengfeng Cao; Yue Liu; Enyu Tian; Yaping Wang; Shunlin Ren; Yongjie Wang; Huajun Zheng; Lanming Chen (Food Control, 2025)

Unveiling the stepwise catalysis of Ni Fe bimetallic single-atom sites toward high-efficiency lithium–sulfur batteries - Yaping Yan; Yi Yang; Zhihui Zhang; Changzheng Xin; Nan Yang; Tianwei He; Shude Liu; Zixu Sun; Yusuke Yamauchi; Ling Kang (Chemical Engineering Journal, 2025)

Impacts of nitrate on methane production and microbial communities in paddy soil - Wenjia Zhao; Lang Liu; Zhidong Liang; Jian Sun; Yi Wang; Hua Chen; Yaping Zhang; Yong Yuan (Journal of Soils and Sediments, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

The dual-function of VN catalytic sites at cathode and anode toward high-performance lithium‑sulfur batteries - Yaping Yan; Yi Yang; Liu Yang; Xuefeng Luo; Guangzhao Wang; Qingquan Xue; Andreu Cabot; Hua Kun Liu; Shi Xue Dou; Zixu Sun (Chemical Engineering Journal, 2025)

MXene-decorated carbonized MOF nanofluids with hybrid ionic liquids for enhanced solar-thermal conversion - Fangfang Su; Jiahe Liang; Zhongjie He; Yangyang Xin; Yisong Liu; Weirui Zhang; Zhuojun Mao; Lijun Yuan; Yaping Zheng; Xiaoqian Li (Chemical Engineering Journal, 2025)

Mo-Nitrogen nexus: Nanotechnology enhanced Mo-based nitrogen fixation towards environmental sustainability - Samina Irshad; Yu Xie; Yaping Lyu; Ziqi Zhang; Xingxin Liu; Haojie Wei; Beza Tuga; Christy L. Haynes; Yaqi Jiang; Yi Sun; Jason C. White; Yukui Rui; et al. (Chemical Engineering Journal, 2025)

A multi-algorithm fusion approach for identifying post-earthquake rainfall-induced debris flow catchments - Huaqiang Yin; Wei Zhou; Renwen Liu; Yaping Zhou; Ming Chen; Zhangqiang Peng (Bulletin of Engineering Geology and the Environment, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Transcription factor OxyR regulates peroxidase levels to enhance Brucella's defense against oxidative stress - Yunyi Zhai; Hui Wang; Guangdong Zhang; Bin Li; Ziyang Diao; Lei Chen; Lulu Tian; Feijie Zhi; Junmei Li; Dong Zhou; Wei Liu; Yaping Jin; et al. (Veterinary Microbiology, 2025)

Reuse of waste corn stalk as heavy metal adsorbent by sulfydryl modification: Optimization of adsorption performance and adsorption mechanism - Xiuyun Liu; Gang Wang; Bigui Wei; Yaping Yan; Liang Dai (Process Safety and Environmental Protection, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Impact of transient flow on bimolecular reactive transport in varying-aperture fractures - Yajing Liu; Jiazhong Qian; Yong Liu; Lei Ma; Yaping Deng; Hailong Chen (Journal of Hydrology, 2025)

Hydrophobic and hydrophilic dissolved organic matter: Mechanistic insights into its influence on sediment phosphorus release revealed through multifaceted characterization - Jing Liu; Yuntao Luo; Yiru Wang; Lixin Jiao; Weizhen Zhang; Liansheng He; Yunxing Xiao; Yaping Liu; Xinxin Huang (Journal of Cleaner Production, 2025)

Chemical composition and functional properties of protein-polyphenol complexes from purple rice: Effects of alkaline and enzymatic extraction - Yongchao Wang; Long Sun; Jianhong Peng; Zhengxuan Wang; Tianrui Zhao; Jianxin Cao; Yaping Liu; Guiguang Cheng; Charles Brennan (Food Chemistry, 2025)

Environmental tobacco smoke exposure in pregnant women and thyroid hormone levels in newborn cord blood: A birth cohort in China - Tengwei Gui; Yan Li; Yaping Liu; Jirong Li; Tong Luo; Shuqi Chen; Xiaoxiao Song; Xia Xiao (Environmental Pollution, 2025)

Multifunctional MOF-based superhydrophobic quartz sand: Interfacial interactions for durable and efficient microplastic removal in stormwater - Yaping Yan; Xiuyun Liu; Xiaojuan Wang; Haiyan Wen; Gang Wang; Liang Dai; Suxia Gao; Tingting Zhang; Bigui Wei (Chemical Engineering Journal, 2025)

Bio-inspired spore-like CoSe2@CNFs heterostructure enabling ultra-stable and high-rate sodium-ion batteries - Enze Ren; Yu Chen; Yaping Zeng; Zhenyao Wang; Wanquan Liu; Heng Wang; Jianrong Xiao; Liu Wang (Chemical Engineering Journal, 2025)

Determination and Application of a New Drought Resistant Control Water Level for Multi-Reservoir Systems Based on a Water Resource Allocation Model - Yaping Cheng; Ziqi Yan; Denghua Yan; Miao Liu; Ruishen Wei (Water Resources Management, 2025)

Fine root length density and production surpass root exudates to shape soil aggregate stability in a warm-temperate natural oak forest under multi-year drought conditions - Xiaomin Gao; Xiuqing Nie; Yi Wang; Cuiju Liu; Yaping Di; Zhicheng Chen; Baoliang Niu; Shirong Liu (Plant and Soil, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Electro-enhanced adsorption and ionization-promoted hydrolysis for 3-cyanopyridine in high-salinity wastewater: Process optimization and mechanistic insights - Yaping Guo; Xinhua Huang; Hongying Chen; Mengyao Ren; Xiang Liu; Xiaoxiao Zhai; Kanming Wang (Journal of Water Process Engineering, 2025)

Mutation in maize chloroplastic polypeptide chain release factor (ZmcpRF1) affects chloroplast development and leaf color - Hao Chen; Haixiao Dong; Xiaohui Shan; Yuan Jiang; Shipeng Li; Hongkui Liu; Shengzhong Su; Yaping Yuan (Planta, 2025)

Inversion of aboveground biomass of Spartina alterniflora based on multispectral UAV - Ziyao Chen; Yan Gu; Jianchun Chen; Dingchen Liu; Junjie Rui; Shibing Zhu; Yaping Wang (Acta Oceanologica Sinica, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Polysaccharide from discarded tobacco leaves and its anti-TMV activities - Yan Wang; Zhengxuan Wang; Yaping Liu; Charles Brennan; Jueting Liu; Jinhong Zhou; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2025)

Characteristics and inhalation risk of aldehydes and ketones in fumes from heated cooking rapeseed oils with different refining levels: Focusing on non-acylglycerol components - Yaping Lv; Yuanyi Xiong; Shufan Luo; Zuqing Zhang; Zhan Ye; Yuanfa Liu (Food Chemistry, 2025)

Effect of labor migration on famers’ biopesticide application --mediating effect based on social network - Ruixin Zhang; Yexing Yin; Yushi Chen; Jinyang Sun; Yuying Liu; Xinhong Fu; Yaping Wang (Environment, Development and Sustainability, 2025)

Condition assessment of corroded spanning subsea pipelines under vortex-induced vibration - Xinhong Li; Runquan Li; Yaping Hu; Ziyue Han; Xiuquan Liu; Yuanjiang Chang (Ocean Engineering, 2025)

Physical aeration mechanism of SDBS wastewater in a tank aerated by a microporous tube system - Yaping Guo; Mengyao Ren; Chenglang Huang; Xinhua Huang; Xiang Liu; Xiaoxiao Zhai; Qingrong Shu (Chemical Engineering Journal, 2025)

Density functional theory and machine learning method for the rapid screening of dual-atom catalysts in N2 electroreduction - Qingchen Li; Nan Xia; Yaping Zhu; Yan Gao; Yahui Liu; Haifeng Wang (Chemical Engineering Journal, 2025)

Does urbanization of tourism-oriented cities promote urban ecological resilience? Observations, judgments, and verifications - Yaping Zhang; Jianjun Zhang; Yuhuan Geng; Shidong Liu; Kexin Yi; Mingyu Meng; Yufei Li (Journal of Geographical Sciences, 2025)

From victims to protectors: Microalgae's unexpected capacity for diuron elimination - Zhangzhang Xie; Cuiyun Yang; Ju Zhang; Yaping Zhang; Oumei Wang; Ying Wang; Fanghua Liu (Journal of Hazardous Materials, 2025)

Foam-based mustard essential oil microcapsules preparation, characterization, grilling application and comparison with emulsion microcapsules - Xiaolong Zhong; Min Zhang; Chung Lim Law; Yaping Liu (Food Chemistry, 2025)

ICPINN: Integral conservation physics-informed neural networks based on adaptive activation functions for 3D blood flow simulations - Youqiong Liu; Li Cai; Yaping Chen; Qixing Chen (Computer Physics Communications, 2025)

Synthesis of a novel tricarboxylic acid monomer and construction of branched polybenzimidazole membranes for vanadium redox flow battery - Huiting Li; Jun Long; Wenheng Huang; Xiyang Liu; Jinchao Li; Liang Chen; Qin Chen; Qianqian Liang; Zhengjin Yang; Yaping Zhang (Chemical Engineering Journal, 2025)

Biochar and PGPR Influence Rhizosphere Bacteria and Synergistically Regulate Tomato Seedling Biomass Under Greenhouse Conditions - Zhenlu Yan; Yuyuan Xing; Changli Ma; Xin Li; Yaping Duan; Xue Wang; Minghao Liu; Muhammad Khashi u Rahman; Xingang Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Quantitative climate reconstruction of the Mid- to late Holocene based on pollen records from Northern Shandong, China - Yaping Li; Wenhao Zheng; Wenfei Liu; Kai Su; Wei Liu; Junna Zhang; Kai Ning; Zhenjing Yang; Guiyun Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Tyrosinase inhibition and enzyme kinetics of red rice bran protein peptides: Mechanism, identification, in silico exploration, and experimental validation - Zhenhao Zhao; Junbo Hu; Huimin Cui; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Bioscience, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Enhancing cardiac regeneration: direct reprogramming of fibroblasts into myocardial-like cells using extracellular vesicles secreted by cardiomyocytes - Yao Yao; Yuexin Yu; Yaping Xu; Yingtian Liu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Vegetation and climate dynamics in Southwestern China during the Han and Jin Dynasties (202 BC-AD 420): Insights from the Spore-pollen and hydrological records from the Chengba site - Junna Zhang; Liu Qi; Yaping Li; Weidong Chen; Luhong Zheng; Xueran Wang; Songhan Li; Bingyuan Zhang (Quaternary International, 2025)

Impact of Drought on Farmers’ Livelihood Vulnerability: A Case Study of County-level Units in Western Jilin Province, China - Jiani Zhang; Yang Han; Yangang Fang; Yaping Xu; Chunlin Chen; Zhuxin Liu; Feiyu Wang; Lijuan Zhuang; Fang Huang (Chinese Geographical Science, 2025)

Research on the spatial correlation network and its driving factors for synergistic development of pollution reduction, carbon reduction, greening, and growth in China's tourism industry - Ying Li; Shizhuan Hao; Yaping Liu; Beilei Chen; Tongqian Zou (Journal of Environmental Management, 2025)

A dual-functional monomer-based molecularly imprinted fluorescent aptasensor employing near-infrared carbon dots for selective detection of quinine in food - Xuyuan Sun; Hao Liu; Zhengyuan Dai; Ying Wang; Li Li; Yaping Ding (Food Chemistry, 2025)

Spatio-temporal variations of heat extremes across the yangtze river delta during 2001–2023 based on remotely sensed seamless air temperature - Chenlu Xu; Yongming Xu; Yaping Mo; Meng Ji; Yonghong Liu; Shanyou Zhu (Environmental Research, 2025)

Rainfall intensities determine accuracy of canopy interception simulation using the Revised Gash model - Mengliang Ma; Qiang Li; Yaping Wang; Jin Liang; Jiangyao Wang; Jinliang Liu; Mingfang Zhang (Agricultural and Forest Meteorology, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Tankyrase inhibitor IWR-1 modulates HIPPO and Transforming Growth Factor β signaling in primed bovine embryonic stem cells cultured on mouse embryonic fibroblasts - Yao Xiao; Yujie Wang; Minghao Zhang; Yan Zhang; Zhihua Ju; Jinpeng Wang; Yaran Zhang; Chunhong Yang; Xiuge Wang; Qiang Jiang; Yaping Gao; Xiaochao Wei; et al. (Theriogenology, 2025)

Seismic geomorphology and reservoir conditions of a Middle Miocene submarine channel system in the Taranaki basin, New Zealand - Guangxu Wang; Wei Wu; Quan Li; Weiqing Liu; Yongsheng Zhou; Shiqin Liang; Yaping Sui (Marine and Petroleum Geology, 2025)

Online SFE-SFC-MS/MS analysis of pyraclostrobin and chiral mefentrifluconazole residues in mango and mango juice - Hao Yang; Yue Geng; Shu Lin; Lu Wang; Yi Peng; Yaping Xu; Wei Jing; Jing Wei; Zeying He; Xiaowei Liu (Food Chemistry, 2025)

Comparative study of different pretreatment methods on peanut oil quality characteristics, anti-oxidation attributes, and phenolic compound compositions - Mingfei Hao; Yaping Lv; Yuanyi Xiong; Yuanfa Liu; Yong-Jiang Xu; Zhan Ye (Food Chemistry, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

Synergistic effects of carbon and heat under disturbance of human activities: Evidence from a resource-based city of China - Yaping Zhang; Jianjun Zhang; Wei Chen; Sen Liang; Kexin Yi; Shidong Liu (Environmental Pollution, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Gold nanoparticle-catalyzed oxidative esterification of furfural: Enhancement by NaOH-etched γ-Al2O3 support - Xianjie Li; Bingxiao Feng; Hailin Zhang; Yaping Liu; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2025)

Silver nanoparticle-functionalized covalent organic frameworks for the inhibition of foodborne pathogenic bacteria and their application in green grape preservation - Jiayi Zhou; Sai Zhang; Yu Zhang; Tianliang Liu; Shuying Yang; Gaopeng Lv; Yaping Wang; Kewei Feng; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Chemistry, 2025)

A hybrid mechanism-based and data-driven model for efficient indoor temperature distribution prediction with transfer learning - Yaping Liu; Jiang Wu; Zhanbo Xu; Yuanjun Shen; Xiaohong Guan (Energy and Buildings, 2025)

A flexible humidity-resistant nanofiber-based triboelectric nanogenerator with high electrical output stability as self-powered sensors for motion monitoring - Yue Sun; Zicheng Qian; Yuna Wang; Yaping Li; Yide Zheng; Yong Liu (Chemical Engineering Journal, 2025)

An ultrathin conformal layer of dry-coated Li+-conductive glass–ceramic for single-crystalline nickel-rich cathode towards all-solid-state lithium batteries - Yaping Wang; Jianxiang Ding; Xiong Xiong Liu; Mufan Cao; Min Gao; Long Pan; ZhengMing Sun (Chemical Engineering Journal, 2025)

Predictive modeling of river blockage severity from debris flows: Integrating statistical and machine learning approaches with insights from Sichuan Province, China - Wei Zhou; Yaping Zhou; Renwen Liu; Huaqiang Yin; Haowen Nie (CATENA, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Occurrence and distribution of atrazine in groundwater from agricultural areas in China - Shengpin Li; Fuyang Huang; Haitao Piao; Wenpeng Li; Fei Liu; Qianying Zhu; Yaping He; Jialin Wang; Maohua Yan (Science of The Total Environment, 2024)

Global patterns of lake microplastic pollution: Insights from regional human development levels - Dan Chen; Ping Wang; Shiqi Liu; Rui Wang; Yaping Wu; A-Xing Zhu; Chunnuan Deng (Science of The Total Environment, 2024)

Conceptual design of an improved ammonia refining process for coal chemical wastewater - Jingtao Guo; Chao Pan; Yaping Liu; Xingming Jin; Bingxiao Feng; Hengjun Gai (Journal of Water Process Engineering, 2024)

One-step synthesis of iron and carbon-quantum-dot co-decorated graphitic carbon nitride photocatalysts for carbamazepine degradation - Xiaoli Liu; Yaping Wang; Yutao Xie; Tiefeng Xu; Yan Gu; Wangyang Lu (Journal of Environmental Chemical Engineering, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Graphene materials as a novel and efficient adsorbent for the chlorophyll removal from rapeseed oil: Adsorption performance and mechanism - Yaping Lv; Shufan Luo; Yuanyi Xiong; Zhan Ye; Yuanfa Liu; Zuqing Zhang (Food Bioscience, 2024)

Biochanin A Attenuates Psoriasiform Inflammation by Regulating Nrf2/HO-1 Pathway Activation and Attenuating Inflammatory Signalling - Yaping Lv; Yingsheng Xu; Songchun Liu; Xianjing Zeng; Bin Yang (Cell Biochemistry and Biophysics, 2024)

Removal strategies for the undesirable components from the crude vegetable oils: A review - Yaping Lv; Zhan Ye; Shufan Luo; Yuanyi Xiong; Yuanfa Liu; Zuqing Zhang (Journal of Cleaner Production, 2024)

One-step hydrothermal synthesis of nitrogen-doped carbon-quantum-dots for detection and efficient removal of high-concentrations nicotine from tobacco wastewater under visible light - Xiaoli Liu; Yaping Wang; Yan Gu; Wangyang Lu (Chemical Engineering Journal, 2024)

The nature of synergy effects between VO and TiO2 in low temperature NH3-SCR reaction - Yingying Jin; Jiaying Li; Kaihao Fan; Yong Chen; Yaping Yang; Xuesong Liu (Journal of Environmental Chemical Engineering, 2024)

Status and trends of artificial intelligence in the R & D of future fruit & vegetable juice - Huanhuan Niu; Min Zhang; Qi Yu; Yaping Liu (Innovative Food Science & Emerging Technologies, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

The influences of extraction methods on the chemical constituents of Lyonia ovalifolia (wall.) Drude and intracellular protective effects based on metabolomics analysis - Chunyan Li; Mengcheng Li; Zhenhao Zhao; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Chemistry, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

A novel “pore-carrier transfer” strategy for preparation of porous liquids toward efficient CO2 capture - Yangyang Xin; Dechao Wang; Weirui Zhang; Fangfang Su; Jing Zhang; Yisong Liu; Wendi Fan; Xiaoqian Li; Libing Qian; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Rational tailoring of spin-polarized photoelectrode for magnetic-assisted overall water splitting - Kehui Xue; Lianqing Yu; Chong Liu; Huihua Luo; Yaping Zhang; Haifeng Zhu; Wei Xing (Chemical Engineering Journal, 2024)

Mechanism of probiotics in the intervention of colorectal cancer: a review - Qinqin Li; Dongmei Liu; Minghua Liang; Yichao Zhu; Muhammad Yousaf; Yaping Wu (World Journal of Microbiology and Biotechnology, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Synthesis of P-Rich Carbon Quantum Dots for Sensitive Fluorescent Detection of 2-Methylimidazole - Zhengyuan Dai; Hao Liu; Xuyuan Sun; Ying Wang; Jie Fan; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Regulation of nitrogen metabolism by COE2 under low sulfur stress in Arabidopsis - Vincent Ninkuu; Yaping Zhou; Hao Liu; Susu Sun; Zhixin Liu; Yumeng Liu; Jincheng Yang; Mengke Hu; Liping Guan; Xuwu Sun (Plant Science, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Bacterial community network complexity and role of stochasticity decrease during primary succession - Yucheng He; Binu M. Tripathi; Jie Fang; Zihao Liu; Yaping Guo; Yue Xue; Jonathan M. Adams (Soil Ecology Letters, 2024)

Effects of nanoplastic exposure during pregnancy and lactation on neurodevelopment of rat offspring - Lei Tian; Yaping Zhang; Jiang Chen; Xuan Liu; Huipeng Nie; Kang Li; Huanliang Liu; Wenqing Lai; Yue Shi; Zhuge Xi; Bencheng Lin (Journal of Hazardous Materials, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Isolation and structural characterization of flavonoids from E Se tea and their synergistic inhibitory effects on lipid accumulation via regulating AMPK/ACC pathway - Jiaxiong Zhang; Jinke Zhang; Xiaoqian Wang; Taiming Chen; Zhengxuan Wang; Yaping Liu; Guiguang Cheng (Food Bioscience, 2024)

Phytochemicals from the rhizome of Bletilla formosana and their antioxidant, cytoprotective and anti-inflammatory activities - Yiqian Li; Luya Qiu; Yifen Wang; Zhengxuan Wang; Guiguang Cheng; Yaping Liu (Food Bioscience, 2024)

A simulation system to study the types and causes of browning in concentrated orange juice during storage - Yangyang Chen; Min Zhang; Arun S. Mujumdar; Yaping Liu (Food and Bioproducts Processing, 2024)

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Evaluating warming trend over the tibetan plateau based on remotely sensed air temperature from 2001 to 2020 - Yan Xin; Yongming Xu; Xudong Tong; Yaping Mo; Yonghong Liu; Shanyou Zhu (Climatic Change, 2024)

Neg1 overexpression in Trichoderma harzianum T4 enhanced its ability to produce spores and antagonistic activity against phytopathogenic fungi - Jingwen Liu; Yaping Wang; Shouquan Lu; Xiaoxu Liu; Henan Zhang; Wei Wang (Archives of Microbiology, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

Retraction notice to ‘Inhibition effects of long-term calcium-magnesia phosphate fertilizer application on Cd uptake in rice: regulation of the iron-nitrogen coupling cycle driven by the soil microbial community’ - Changrong Wang; Yongchun Huang; Changbo Zhang; Yahui Zhang; Kai Yuan; Weijie Xue; Yaping Liu; Yuemin Liu; Zhongqi Liu (Journal of Hazardous Materials, 2024)

A new strategy to improve the quality of frozen chicken wings: High voltage electrostatic field combined with phosphorus-free water retaining agent - Jiangshan Qiao; Min Zhang; Dongbei Shen; Yaping Liu (Food Research International, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Controlling release of astaxanthin in β-sitosterol oleogel-based emulsions via different self-assembled mechanisms and composition of the oleogelators - Shujie Wang; Yuyue Qin; Yaping Liu; Guoqin Liu; Guiguang Cheng; Thanapop Soteyome (Food Research International, 2024)

Efficient separation of cresol isomers using azeotropic coupling pressure-swing distillation: From separation mechanism to process integration - Chao Pan; Jingtao Guo; Yaping Liu; Bingxiao Feng; Guoxuan Li; Hengjun Gai; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2024)

Development of food-grade xylanase encapsulation using electrospray dextran microparticles - Yaping Zhang; Chun Liu; Yingjie Lin; Hong Wu; Ying Lin; Fengguang Zhao; Shuangyan Han (Food Hydrocolloids, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Distribution and source of heavy metals in Tibetan Plateau topsoil: New insight into the influence of long-range transported sources to the surrounding glaciers - Xiaoli Liu; Wenhua Gao; Ting Wei; Zhiwen Dong; Jiawen Ren; Yaping Shao; Xuejiao Chen (Environmental Pollution, 2024)

High spatiotemporal asynchrony between water deficit and nitrate accumulation under apple orchards in deep loess deposits - Wangjia Ji; Yaping Wang; Ruifeng Li; Wenzhao Liu; Zhi Li (CATENA, 2024)

Optimizing City-Scale Demolition Waste Supply Chain Under Different Carbon Policies - Jingkuang Liu; Yaping Chai; Jiaxi Zheng; Jiazhuo Dai; Zhenshuang Wang (Environmental Science and Pollution Research, 2024)

LncRNA STAT3-AS regulates endometrial receptivity via the STAT3 signaling pathway - Yanni Jia; Wei Wang; Jiaqi Jiang; Xinyan Zhang; Haijing Li; Suhua Gong; Zuhui Li; Haokun Liu; Chunmei Shang; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2024)

Relationship of environmental exposure temperature and temperature extremes on sperm DNA fragmentation index in men with different BMI values and the indirect effect of DNA fragmentation index on semen parameters - Chen Wang; Qiwei Yu; Ting Chu; Fang Wang; Fangli Dong; Hang Xin; Di Wang; Yaping Liu; Jun Zhai (Science of The Total Environment, 2024)

The shape of reactive nitrogen losses from intensive farmland in China - Xiaoying Zhan; Qingwen Zhang; Ming Li; Xikang Hou; Ziyin Shang; Zhen Liu; Yaping He (Science of The Total Environment, 2024)

Oxidative esterification of 5-hydroxymethylfurfural to dimethyl 2,5-furandicarboxylate over Au-supported poly(ionic liquid)s - Yaping Liu; Chao Pan; Xiaomin Qiu; Xianjie Li; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

Distinct biogeographic patterns in Glomeromycotinian and Mucoromycotinian arbuscular mycorrhizal fungi across China: A meta-analysis - Zihao Liu; Jie Fang; Yucheng He; Gary D. Bending; Bin Song; Yaping Guo; Xiaojie Wang; Zemin Fang; Jonathan M. Adams (Science of The Total Environment, 2024)

Composition analysis and health risk assessment of the hazardous compounds in cooking fumes emitted from heated soybean oils with different refining levels - Shufan Luo; Zhan Ye; Yaping Lv; Yuanyi Xiong; Yuanfa Liu (Environmental Pollution, 2024)

A Review of Electrochemical Treatment Processes of Leachate Membrane Concentrate - Peixin Tang; Xu Ren; Zhicheng Pan; Meng Shen; Danni Peng; Yucheng Liu; Yaping Zhong; Yumei Peng; Xin Peng (Water, Air, & Soil Pollution, 2024)

Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2024)

Functional characterization of polyol/monosaccharide transporter 1 in Lotus japonicus - Leru Liu; Shaoming Xu; Lu Tian; Xuelian Qin; Guojiang Wu; Huawu Jiang; Yaping Chen (Journal of Plant Physiology, 2024)

Fisetin, a dietary flavonoid, promotes transintestinal cholesterol excretion through the activation of PPARδ - Yao Guo; Bing Liu; Yaping Geng; Ke Chen; Junyan Li; Xiangju Yin; Shenshen Zhang (Food Research International, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

Engineered structural carbon aerogel based on bacterial Cellulose/Chitosan and graphene Oxide/Graphene for multifunctional piezoresistive sensor - Qixuan Xiang; Hao Zhang; Zhiyuan Liu; Yaping Zhao; Huijun Tan (Chemical Engineering Journal, 2024)

An assessment of natural and anthropogenic influences on atmospheric fluoride deposition in central Tibetan Plateau during 1951–2008 A.D. using the Zangser Kangri ice core - Xiang Zou; Wangbin Zhang; Shuangye Wu; Jinhai Yu; Jing Song; Hongxi Pang; Yaping Liu; Shugui Hou (Atmospheric Environment, 2024)

Water deficit limits soil organic carbon sequestration under old apple orchards in the loess-covered region - Ruifeng Li; Yaping Wang; Wangjia Ji; Wenzhao Liu; Zhi Li (Agriculture, Ecosystems & Environment, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Valorization of meat and bone residue by ultrasound and high voltage electrostatic field assisted two-stage enzymatic hydrolysis: Nutritional characteristics and flavor analysis - Tiantian Tang; Min Zhang; Yaping Liu (Food Bioscience, 2023)

The investigation of circRNA profiling reveals the regulatory role of the hsa_circ_0000375/miR-7706 pathway in breast cancer - Haoqi Wang; Fei Liu; Jing Xue; Yaping Liu; Wei Gao; Shan Yang; Yunzhe Mi; Xi Zhang; Shan Gao; Cuizhi Geng (Molecular Biology Reports, 2023)

Cytotoxic 4-phenylcoumarins from the flowering buds of Mesua ferrea - Xiya Chen; Zhiying Liu; Bi Zhong; Mengjie Zhu; Han Yao; Xiaojie Chen; Yongchao Lu; Shuyun Wang; Yaping Guo (Natural Product Research, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Pore size-tunable core-shell structured Ni-Ru Nanoparticles catalyst for the reductive amination of isosorbide diketone - Peng Liu; Hongyu Zhang; Yaping Han; Jiquan Zhao; Yuecheng Zhang (Chemical Engineering Journal, 2023)

Apple trees can extract soil water from both deep layers and neighboring cropland in the tableland region of Chinese Loess Plateau - Yaping Wang; Xiaoyang Han; Weiming Yan; Liping Cheng; Xingdong Dang; Wenzhao Liu (CATENA, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

ALPK1 Expressed in IB4-Positive Neurons of Mice Trigeminal Ganglions Promotes MIA-Induced TMJ pain - Taomin Zhu; Huimin Li; Yuxiang Chen; Xueke Jia; Xiaohan Ma; Xin Liu; Yaping Feng; Jin Ke (Molecular Neurobiology, 2023)

Impact of the producer services agglomeration on PM2.5: A case study of the Yellow River Basin, China - Yan Liu; Yu Cheng; Ruijing Zheng; Huaxue Zhao; Yaping Wang (Journal of Geographical Sciences, 2023)

Comparison of gap-filling methods for producing all-weather daily remotely sensed near-surface air temperature - Yaping Mo; Yongming Xu; Yonghong Liu; Yan Xin; Shanyou Zhu (Remote Sensing of Environment, 2023)

Synergistic catalytic wet oxidation of ammonia over carbon-supported low-loading Ru/Cu bimetallic catalyst - Donglin Yang; Bingxiao Feng; Yaping Liu; Chaoting Deng; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Journal of Environmental Chemical Engineering, 2023)

Effect of pore-throat structure on air-foam flooding performance in a low-permeability reservoir - Guangfeng Liu; Yaping Ding; Juntao Wang; Lizhen Ge; Xiaoming Chen; Daoyong Yang (Fuel, 2023)

Phosphate functionalized silicide for efficient removal of uranium contamination from hypersaline effluents at ultralow dosage - Yaping Jian; Yue Ma; Meng Cao; Shilei Zhao; Qin Peng; Hui Wang; Tao Liu; Yihui Yuan; Ning Wang (Chemical Engineering Journal, 2023)

Noncovalent co-assembly of aminoglycoside antibiotics@tannic acid nanoparticles for off-the-shelf treatment of pulmonary and cutaneous infections - Guang Yang; Changrong Wang; Yaping Wang; Xiaoqing Liu; Ye Zhang; Ming Xu; Hongzhang Deng; Weiwei Wang (Chemical Engineering Journal, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

The Secondary Motor Cortex-striatum Circuit Contributes to Suppressing Inappropriate Responses in Perceptual Decision Behavior - Jing Liu; Dechen Liu; Xiaotian Pu; Kexin Zou; Taorong Xie; Yaping Li; Haishan Yao (Neuroscience Bulletin, 2023)
The secondary motor cortex (M2) encodes choice-related information and plays an important role in cue-guided actions. M2 neurons innervate the dorsal striatum (DS), which also contributes to decision-making behavior, yet how M2 modulates signals in the DS to influence perceptual decision-making is unclear. Using mice performing a visual Go/No-Go task, we showed that inactivating M2 projections to the DS impaired performance by increasing the false alarm (FA) rate to the reward-irrelevant No-Go stimulus. The choice signal of M2 neurons correlated with behavioral performance, and the inactivation of M2 neurons projecting to the DS reduced the choice signal in the DS. By measuring and manipulating the responses of direct or indirect pathway striatal neurons defined by M2 inputs, we found that the indirect pathway neurons exhibited a shorter response latency to the No-Go stimulus, and inactivating their early responses increased the FA rate. These results demonstrate that the M2-to-DS pathway is crucial for suppressing inappropriate responses in perceptual decision behavior.

HIF-1α–PPARγ–mTORC1 signaling pathway-mediated autophagy induces inflammatory response in pancreatic cells in rats with hyperlipidemic acute pancreatitis - Yumei Ma; Xiaolin Li; Zhilan Liu; Xiaohong Xue; Yaping Wang; Yingcai Ma (Molecular Biology Reports, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Inhibition of soluble calcium ions in municipal solid waste incineration fly ash by carbonate in an electrokinetic environment - Qingxiang Wang; Shilin Wang; Yifan Zhang; Junqi Liu; Yaping Guo; Tao Huang; Yaojie Tu; Xin He; Ding Wang (Fuel, 2023)

Protective effect of hot-water and ethanol-aqueous extracts from Anneslea fragrans against acetaminophen-induced acute liver injury in mice - Yiwen Hu; Mengcheng Li; Yongpeng Wang; Qingwang Xue; Xiaodong Luo; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Yudan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

How does digitalization drive carbon emissions? The inverted U-shaped effect in China - Ruijing Zheng; Ge Wu; Yu Cheng; Haimeng Liu; Yaping Wang; Xinyang Wang (Environmental Impact Assessment Review, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Phase engineering of 1 T-MoS2 on BiVO4 photoanode with p–n Junctions: Establishing high speed charges transport channels for efficient photoelectrochemical water splitting - Lianqing Yu; Kehui Xue; Huihua Luo; Chong Liu; Heyuan Liu; Haifeng Zhu; Yaping Zhang (Chemical Engineering Journal, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Scalable production of polyamide-6/graphene composites with enhanced electromagnetic shielding and thermal conductivity - Rahul Navik; Huijun Tan; Hao Zhang; Zhiyuan Liu; Qixuan Xiang; Liyun Shi; Shiming Lu; Yaping Zhao (Chemical Engineering Journal, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Maillard reaction products of pea protein hydrolysate as a flavour enhancer for beef flavors: Effects on flavor and physicochemical properties - Zhiliang Zheng; Lihui Zhang; Min Zhang; Arun S. Mujumdar; Yaping Liu (Food Chemistry, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Ecological risk assessment of potentially toxic elements in selenium-rich soil with different land-use types - Jinming Zhang; Wen Ge; Chen Xing; Yuan Liu; Xiaofei Shen; Bing Zhao; Xinyu Chen; Yaping Xu; Shoubiao Zhou (Environmental Geochemistry and Health, 2023)

One‐kilometre monthly air temperature and precipitation product over the Mongolian Plateau for 1950–2020 - Ying Xin; Yaping Yang; Xiaona Chen; Xiafang Yue; Yangxiaoyue Liu; Cong Yin (International Journal of Climatology, 2023)
The fragile ecological environment of the Mongolian Plateau (MP) is sensitive to climate change. It is necessary to fully understand the temperature and precipitation changes on the MP to ensure regional sustainable development. Most existing studies are conducted based on station observations which suffer from sparse distribution and limited spatial representativeness and cannot perfectly represent the climatic conditions of the whole region. By contrast, the long‐term, spatially continuous reanalysis products offer new opportunities for MP climate change research. However, the coarse spatial resolution and large uncertainties of reanalysis data limit their applicability to provide reliable climate information at finer scales. Within the delta downscaling framework, we downscale and correct the state‐of‐the‐art European Centre for Medium‐range Weather Forecasts ReAnalysis 5 land portion (ERA5‐Land) using a high‐resolution WorldClim reference climatology and generate a long‐term (1950–2020) 1‐km monthly air temperature and precipitation downscaled dataset. During the downscaling process, the results obtained by nearest neighbour, bilinear and bicubic interpolation methods are evaluated and compared. Air temperature result of bilinear method and precipitation result of nearest neighbour method, which have the best accuracy, are taken as the final downscaled data. The evaluation shows that the downscaled data has acceptable accuracy (overall MBE = −0.41°C, Corr = 0.997, RMSE = 1.51°C for air temperature, and MBE = 1.58 mm·month −1 , Corr = 0.747, RMSE = 24.24 mm·month −1 for precipitation), and outperforms the original ERA5‐Land and widely used Climatic Research Unit (CRU) data. In addition, the downscaled data can also provide accurate and detailed temperature and precipitation change trends over the MP. With fine spatial resolution, long‐time span and good spatial continuity, the downscaled air temperature and precipitation will be a useful data source to explore climate change over the MP.

Mettl3-mediated transcriptome-wide m6A methylation induced by cigarette smoking in human bronchial epithelial cells - Yaping Zhang; Lixing Wang; Yifei Liu; Furong Yan (Toxicology in Vitro, 2023)

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

Effects of ultrasound combined technology on quality and volatile compound properties of chili sauce - Tiantian Tang; Min Zhang; Chung Lim Law; Yaping Liu (Food Bioscience, 2023)

Effect of combined zinc oxide nanoparticles using citric acid and microwave heating on the quality of animal fat - Lan Zhang; Min Zhang; Yaping Liu; Zhongxiang Fang (Food Bioscience, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

Long-term manuring enhances soil gross nitrogen mineralization and ammonium immobilization in subtropical area - Jun Wang; Lei Wu; Qiong Xiao; Yaping Huang; Kailou Liu; Yan Wu; Dongchu Li; Yinghua Duan; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

USP18 promotes endometrial receptivity via the JAK/STAT1 and the ISGylation pathway - Xinyan Zhang; Suhua Gong; Haijing Li; Jiaqi Jiang; Yanni Jia; Ruixue Zhang; Haokun Liu; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

A molecular networking-based isolation of gardneria alkaloids from Gardneria distincta and their anti-inflammatory activity - Sifan Teng; Junjie He; Xiaoqian Wang; Yiqian Li; Afsar Khan; Tianrui Zhao; Yudan Wang; Guiguang Cheng; Yaping Liu (Phytochemistry, 2023)

Sorption of bisphenol A onto microplastics and associated environmental risks in comparison to engineered carbonous materials and natural media - Shuai Tang; Shengjia Ma; Tao Zhang; Xuemin Liu; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Gondwana Research, 2023)

Effect of ultra-high pressure pretreatment on the phenolic profiles, antioxidative activity and cytoprotective capacity of different phenolic fractions from Que Zui tea - Yongpeng Wang; Zhengxuan Wang; Qingwang Xue; Li Zhen; Yudan Wang; Jianxin Cao; Yaping Liu; Afsar Khan; Tianrui Zhao; Guiguang Cheng (Food Chemistry, 2023)

Protective effect of Anneslea fragrans ethanolic extract against CCl4-induced liver injury by inhibiting inflammatory response, oxidative stress and apoptosis - Yudan Wang; Xiaocui Deng; Yaping Liu; Yifen Wang; Xiaodong Luo; Tianrui Zhao; Zhengxuan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Storm-driven variations in depositional environments modify pyrite sulfur isotope records - Kaixi Jiang; Chunming Lin; Xia Zhang; Yanyan Zhao; Xianguo Lang; Ming Su; Ce Wang; Yaping Lei; Jiarui Liu (Earth and Planetary Science Letters, 2023)

Improving the uptake of PAHs by the ornamental plant Sedum spectabile using nano-SiO2 and nano-CeO2 - Jianv Liu; Yaping Wang; Mingzhu Wang; Xiaoting Feng; Rongrong Liu; Zijin Xue; Qixing Zhou (Science of The Total Environment, 2023)

Spatial-temporal variability pattern of multi-depth soil moisture jointly driven by climatic and human factors in China - Yangxiaoyue Liu; Yaping Yang (Journal of Hydrology, 2023)

Anthropogenic drought in the Yellow River basin: Multifaceted and weakening connections between meteorological and hydrological droughts - Yaping Wang; Shuai Wang; Yanqiang Chen; Fei Wang; Yanxu Liu; Wenwu Zhao (Journal of Hydrology, 2023)

Neural Network, Nonlinear-Fitting, Sliding Mode, Event-Triggered Control under Abnormal Input for Port Artificial Intelligence Transportation Robots - Yaping Zhu; Qiang Zhang; Yang Liu; Yancai Hu; Sihang Zhang (Journal of Marine Science and Engineering, 2023)
A new control algorithm was designed to solve the problems of actuator physical failure, remote network attack, and sudden change in trajectory curvature when a port’s artificial intelligence-based transportation robots track transportation in a freight yard. First of all, the nonlinear, redundant, saturated sliding surface was designed based on the redundant information of sliding mode control caused by the finite nature of control performance; the dynamic acceleration characteristic of super-twisted sliding mode reaching law was considered to optimize the control high frequency change caused by trajectory mutation; and an improved super-twist reaching law was designed. Then, a nonlinear factor was designed to construct a nonlinear, fault-tolerant filtering mechanism to compensate for the abnormal part of the unknown input that cannot be executed by adaptive neural network reconstruction. On this basis, the finite-time technology and parameter-event-triggered mechanism were combined to reduce the dependence on communication resources. As a result, the design underwent simulation verification to verify its effectiveness and superiority. In the comparative simulation, under a consistent probability of a network attack, the tracking accuracy of the algorithm proposed in this paper was 22.65%, 12.69% and 11.48% higher those that of the traditional algorithms.

Research on synthesis and property of nano-textured Sc2O3-MgO efficient antibacterial agents - Ying Wang; Yanjing Liu; Xiyue Li; Yuezhou Liu; Fuming Wang; Yaping Huang; Bing Du; Yongfang Qian; Lihua Lv (JBIC Journal of Biological Inorganic Chemistry, 2023)

Interferon-τ -induced ISG15-AS regulates endometrial receptivity during early goat pregnancy - Ruixue Zhang; Xinyan Guo; Hanbing Li; Zuhui Li; Suhua Gong; Haijing Li; Yongjie Ma; Haokun Liu; Chuxi Gao; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

The spatial configuration of buildings: A vital consideration impossible to ignore in regulating urban land surface temperature? Evidence from 35 Chinese cities - Wei Chen; Jianjun Zhang; Shidong Liu; Sen Liang; Yaping Zhang; Shu Fu (Science of The Total Environment, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Improved thermal tolerance of ovotransferrin against pasteurization by phosphorylation - Yaping Liu; Jiajie Wang; Chenxin Huang; Bingying Cai; Fuxuan Guo; Lin Chen; Xianchao Feng; Meihu Ma (Food Chemistry, 2023)

Climate warming accelerates cotton growth while cultivar shifts extend the growth period - Wanrui Han; Shengli Liu; Yaping Lei; Yongjiang Zhang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Yabing Li; Zhanbiao Wang (Field Crops Research, 2023)

Simultaneous recovery of nutrients and water from human urine by a novel thermally activated peroxydisulfate and membrane distillation integrated system - Yaping Lyu; Xiuwei Ao; Shikun Cheng; Nana Liu; Yu Men; Zifu Li (Chemical Engineering Journal, 2023)

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Single atomic ruthenium in WO3 boosted hydrogen evolution stability at Ampere-level current density in whole pH range - Hai Liu; Guoying Tan; Mengxuan Li; Zhuang Zhang; Marshet Getaye Sendeku; Yaping Li; Yun Kuang; Xiaoming Sun (Chemical Engineering Journal, 2023)

Genetic diversity and structure of a core collection of Huangqi (Astragalus ssp.) developed using genomic simple sequence repeat markers - Fanshu Gong; Yaping Geng; Pengfei Zhang; Feng Zhang; Xinfeng Fan; Yaling Liu (Genetic Resources and Crop Evolution, 2023)

Environmental-friendly hydrochar-montmorillonite composite for efficient catalytic degradation of dicamba and alleviating its damage to crops - Chunxia Ding; Guangyong Zeng; Yaping Tao; Xiuyu Long; Daoxin Gong; Nan Zhou; Rongying Zeng; Xiangying Liu; Yaocheng Deng; Mei-E Zhong (Science of The Total Environment, 2023)

Carbon layer encapsulation strategy for designing multifunctional core-shell nanorod aerogels as high-temperature thermal superinsulators - Fengqi Liu; Chenbo He; Yonggang Jiang; Yaping Yang; Fei Peng; Lanfang Liu; Jing Men; Junzong Feng; Liangjun Li; Guihua Tang; Jian Feng (Chemical Engineering Journal, 2023)

Spatial and temporal characteristics of nighttime UHII based on local climate zone scheme using mobile measurement-A case study of Changsha - Yaping Chen; Jiayu Li; Yinze Hu; Luyun Liu (Building and Environment, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Global trends, regional differences and age distribution for the incidence of HIV and tuberculosis co-infection from 1990 to 2019: results from the global burden of disease study 2019 - Yaping Wang; Wenzhan Jing; Jue Liu; Min Liu (Infectious Diseases, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Transcriptome Analysis Reveals Differential Gene Expression in Garlic Aerial Bulbs in Response to Gibberellin Application - Yuhui Dong; Hongcheng Fang; Yujiao Hou; Yaping Zhao; Xiudong Sun; Shiqi Liu (Journal of Plant Growth Regulation, 2022)

Development of center pivot irrigation farmlands from 2009 to 2018 in the Mu Us dune field, China: Implication for land use planning - Xiaokang Liu; Zhibao Dong; Yaping Ding; Ruijie Lu; Liyun Liu; Zhiyong Ding; Yijing Li (Journal of Geographical Sciences, 2022)

Biparental genetic mapping reveals that CmCLAVATA3 (CmCLV3) is responsible for the variation in carpel number in melon (Cucumis melo L.) - Lihuan Wang; Yaping Wang; Feishi Luan; Xian Zhang; Jingchao Zhao; Zhongzhou Yang; Shi Liu (Theoretical and Applied Genetics, 2022)

Organophosphate esters in children and adolescents in Liuzhou city, China: concentrations, exposure assessment, and predictors - Meng Yu; Xiang Li; Bingqing Liu; Yaping Li; Ling Liu; Limei Wang; Lulu Song; Youjie Wang; Liqin Hu; Surong Mei (Environmental Science and Pollution Research, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

BMAL1 induces colorectal cancer metastasis by stimulating exosome secretion - Pengjuan Dong; Yaping Wang; Yutong Liu; Chunting Zhu; Jiaxin Lin; Ruizhe Qian; Luchun Hua; Chao Lu (Molecular Biology Reports, 2022)

Path dependence in pro-poor tourism - Yaping Liu; Jie Yu (Environment, Development and Sustainability, 2022)

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

Spatio-temporal analysis of urban air pollutants throughout China during 2014–2019 - Chenkai Zhao; Ying Sun; Yaping Zhong; Senhao Xu; Yue Liang; Shu Liu; Xiaodong He; Jinghai Zhu; Takayuki Shibamoto; Miao He (Air Quality, Atmosphere & Health, 2021)

Pseudomonas aeruginosa outer membrane vesicles ameliorates lung ischemia–reperfusion injury by regulating the balance of regulatory T cells and Th17 cells through Tim-3 and TLR4/NF-κB pathway - Bo Liu; Fengxia Ding; Ding Cao; Jiang Liu; Yaping Wang; Chun Wu (Inflammation Research, 2021)

The influence of VDR polymorphisms on the type 2 diabetes susceptibility in Chinese: an interaction with hypertriglyceridemia - Dongdong Zhang; Cheng Cheng; Yan Wang; Yuan Xue; Yaping Liu; Yiming Liu; Mingming Feng; Ze Xu; Wenjie Li; Xing Li (Molecular Genetics and Genomics, 2021)

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

Structural elucidation of fucoidans from Sargassum pallidum - Xin Liu; Bin Liu; Xiaolei Wei; Yaping Shi; Airong Jia; Changyun Wang (Journal of Applied Phycology, 2021)

A 2-step algorithm combining glutamate dehydrogenase and nucleic acid amplification tests for the detection of Clostridioides difficile in stool specimens - Chengcheng Liu; Chenjie Tang; Yaping Han; Yuqiao Xu; Fang Ni; Ke Jin; Genyan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Docetaxel-loaded D-α-tocopheryl polyethylene glycol-1000 succinate liposomes improve lung cancer chemotherapy and reverse multidrug resistance - Na Li; Yaping Mai; Qiang Liu; Guojing Gou; Jianhong Yang (Drug Delivery and Translational Research, 2021)

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Sediment transport under increasing anthropogenic stress: Regime shifts within the Yellow River, China - Shuang Song; Shuai Wang; Bojie Fu; Yanxu Liu; Kevin Wang; Yikai Li; Yaping Wang (Ambio, 2020)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Core collection construction and evaluation of the genetic structure of Glycyrrhiza in China using markers for genomic simple sequence repeats - Yaling Liu; Yaping Geng; Xiaodong Xie; Pengfei Zhang; Junling Hou; Wenquan Wang (Genetic Resources and Crop Evolution, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

How does energy poverty affect economic development? A panel data analysis of South Asian countries - Asad Amin; Yaping Liu; Jie Yu; Abbas Ali Chandio; Samma Faiz Rasool; Ji Luo; Shah Zaman (Environmental Science and Pollution Research, 2020)

Application of next-generation sequencing to screen for pathogenic mutations in 123 unrelated Chinese patients with Marfan syndrome or a related disease - Jiacheng Li; Chaoxia Lu; Wei Wu; Yaping Liu; Rongrong Wang; Nuo Si; Xiaolu Meng; Shuyang Zhang; Xue Zhang (Science China Life Sciences, 2019)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Population distribution patterns and changes in China 1953–2010 - Cuiling Liu; Yaping Xu; Fahui Wang (Journal of Geographical Sciences, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Analyzing Population Density Disparity in China with GIS-automated Regionalization: The Hu Line Revisited - Fahui Wang; Cuiling Liu; Yaping Xu (Chinese Geographical Science, 2019)

Laboratory experiments demonstrate that the hissing of the Chinese alligator can effectively inhibit movement of flower fish Ptychobarbus kaznakovi - Guoyong Liu; Yujiao Wu; Xiujun Shen; Yaping Hu; XiHuo Qin; Weixin Tian; Liming Liu; Xiaoling Wang; Xiaotao Shi (Hydrobiologia, 2019)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Multi-Modality Cascaded Convolutional Neural Networks for Alzheimer’s Disease Diagnosis - Manhua Liu; Danni Cheng; Kundong Wang; Yaping Wang (Neuroinformatics, 2018)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Purification, characterization, and biocatalytic potential of a novel dextranase from Chaetomium globosum - Liu Yang; Nandi Zhou; Yaping Tian (Biotechnology Letters, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Rational Design and Cyclization of MIG6 Peptide to Restore its Binding Affinity for ErbB Family Receptor Tyrosine Kinases - Dingwa Zhang; Deyong He; Ling Huang; Yaping Xu; Lijun Liu (International Journal of Peptide Research and Therapeutics, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

Water and CO2 fluxes over semiarid alpine steppe and humid alpine meadow ecosystems on the Tibetan Plateau - Lei Wang; Huizhi Liu; Yaping Shao; Yang Liu; Jihua Sun (Theoretical and Applied Climatology, 2018)

A rapid method for establishment of a reverse genetics system for canine parvovirus - Yongle Yu; Jun Su; Jigui Wang; Ji Xi; Yaping Mao; Qiang Hou; Xiaomei Zhang; Weiquan Liu (Virus Genes, 2017)

A novel homozygous complex deletion in CFTR caused cystic fibrosis in a Chinese patient - Keqiang Liu; Yaping Liu; Xue Li; Kai-Feng Xu; Xinlun Tian; Xue Zhang (Molecular Genetics and Genomics, 2017)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

HUCMNCs protect vascular endothelium and prevent ISR after endovascular interventional therapy for vascular diseases in T2DM rabbits - Haixia Ding; Tong Zhang; Yaping Du; Bei Liu; Yueqin Liu; Fujun Wang (Molecular and Cellular Biochemistry, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

Applicability of Perinereis aibuhitensis Grube for fish waste removal from fish cages in Sanggou Bay, P. R. China - Jinghui Fang; Zengjie Jiang; Henrice M. Jansen; Fawen Hu; Jianguang Fang; Yi Liu; Yaping Gao; Meirong Du (Journal of Ocean University of China, 2017)

The response of sedimentary record to catchment changes induced by human activities in the western intertidal flat of Yalu River Estuary, China - Yong Shi; Zhishuai Liu; Jianhua Gao; Yang Yang; Yaping Wang (Acta Oceanologica Sinica, 2017)

Novel rice mutants overexpressing the brassinosteroid catabolic gene CYP734A4 - Wenjing Qian; Chao Wu; Yaping Fu; Guocheng Hu; Zhengquan He; Wenzhen Liu (Plant Molecular Biology, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Ginsenoside Rg1 protects human umbilical cord blood-derived stromal cells against tert-Butyl hydroperoxide-induced apoptosis through Akt–FoxO3a–Bim signaling pathway - Ying Liu; Long Yi; Lu Wang; Linbo Chen; Xiongbin Chen; Yaping Wang (Molecular and Cellular Biochemistry, 2016)

The growth and reproduction performance of TALEN-mediated β-lactoglobulin-knockout bucks - Hengtao Ge; Chenchen Cui; Jun Liu; Yan Luo; Fusheng Quan; Yaping Jin; Yong Zhang (Transgenic Research, 2016)

Isolation and functional characterization of a cold responsive phosphatidylinositol transfer-associated protein, ZmSEC14p, from maize (Zea may L.) - Xiaoyu Wang; Xiaohui Shan; Chunmei Xue; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yuan Jiang; Yanfei Zhang; Yaping Yuan (Plant Cell Reports, 2016)

Genetic characterization of the complete genome of an Aleutian mink disease virus isolated in north China - Ji Xi; Jigui Wang; Yongle Yu; Xiaomei Zhang; Yaping Mao; Qiang Hou; Weiquan Liu (Virus Genes, 2016)

Turbidity maximum formation and its seasonal variations in the Zhujiang (Pearl River) Estuary, southern China - Runqi Liu; Yaping Wang; Jianhua Gao; Ziyin Wu; Weibing Guan (Acta Oceanologica Sinica, 2016)

Environmental remediation potential of Perinereis aibuhitensis (Polychaeta) based on the effects of temperature and feed types on its carbon and nitrogen budgets - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Meirong Du; Yi Liu; Yuze Mao; Yaping Gao; Jianguang Fang (Marine Biology Research, 2016)

Comparison of biological and genomic characteristics between a newly isolated mink enteritis parvovirus MEV-LHV and an attenuated strain MEV-L - Yaping Mao; Jigui Wang; Qiang Hou; Ji Xi; Xiaomei Zhang; Dawei Bian; Yongle Yu; Xi Wang; Weiquan Liu (Virus Genes, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Erratum to: Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

A recombinant canine distemper virus expressing a modified rabies virus glycoprotein induces immune responses in mice - Zhili Li; Jigui Wang; Daoli Yuan; Shuang Wang; Jiazeng Sun; Bao Yi; Qiang Hou; Yaping Mao; Weiquan Liu (Virus Genes, 2015)

Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Pseudooceanicola atlanticus gen. nov. sp. nov., isolated from surface seawater of the Atlantic Ocean and reclassification of Oceanicola batsensis, Oceanicola marinus, Oceanicola nitratireducens, Oceanicola nanhaiensis, Oceanicola antarcticus and Oceanicola flagellatus, as Pseudooceanicola batsensis comb. nov., Pseudooceanicola marinus comb. nov., Pseudooceanicola nitratireducens comb. nov., Pseudooceanicola nanhaiensis comb. nov., Pseudooceanicola antarcticus comb. nov., and Pseudooceanicola flagellatus comb. nov. - Qiliang Lai; Guizhen Li; Xiupian Liu; Yaping Du; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Emcibacter nanhaiensis gen. nov. sp. nov., isolated from sediment of the South China Sea - Xiupian Liu; Guangyu Li; Qiliang Lai; Fengqin Sun; Yaping Du; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Idiomarina atlantica sp. nov., a marine bacterium isolated from the deep sea sediment of the North Atlantic Ocean - Juan Du; Qiliang Lai; Yang Liu; Yaping Du; Xiupian Liu; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

A PCR-based microwell-plate hybrid capture assay for high-risk human papillomavirus - Yumei Wang; Yan Liu; Yaping Ding; Nan Sun; Yafang Gong; Shangxian Gao (Archives of Virology, 2014)

Directed Self-assembled Nanoparticles of Probucol Improve Oral Delivery: Fabrication, Performance and Correlation - Zhiwen Zhang; Shijun Jiang; Zeying Liu; Baohua Niu; Wangwen Gu; Yaping Li; Jingbin Cui (Pharmaceutical Research, 2014)

Actibacterium atlanticum sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Yaping Du; Xiupian Liu; Guangyu Li; Yunbiao Xie; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Aquimarina atlantica sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Xiupian Liu; Yunbiao Xie; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Erratum to: Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2013)

Large-Eddy Atmosphere–Land-Surface Modelling over Heterogeneous Surfaces: Model Development and Comparison with Measurements - Yaping Shao; Shaofeng Liu; Jan H. Schween; Susanne Crewell (Boundary-Layer Meteorology, 2013)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

In vitro potency and efficacy favor later generation fluoroquinolones for treatment of canine and feline Escherichia coli uropathogens in the United States - Xiaoqiang Liu; Dawn M. Boothe; Yaping Jin; Kamoltip Thungrat (World Journal of Microbiology and Biotechnology, 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

Callus induction and shoot organogenesis from anther cultures of Curcuma attenuata Wall - Yaping Kou; Guohua Ma; Jaime A. Teixeira da Silva; Nian Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

The Effects of Ce on the Proliferation, Osteogenic Differentiation and Mineralization Function of MC3T3-E1 Cells In Vitro - Dandan Liu; Jinchao Zhang; Yaping Li; Shuxiang Wang; MengSu Yang (Biological Trace Element Research, 2012)

Downregulation of Cinnamoyl CoA Reductase Affects Lignin and Phenolic Acids Biosynthesis in Salvia miltiorrhiza Bunge - Zhengjun Wang; Langjun Cui; Chen Chen; Xiaojing Liu; Yaping Yan; Zhezhi Wang (Plant Molecular Biology Reporter, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Molecular characterization, expression pattern, polymorphism and association analysis of bovine ADAMTSL3 gene - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Yang Jiao; Kui Li (Molecular Biology Reports, 2012)

Synergistic or Antagonistic Effect of MTE plus TF or Icariin from Epimedium koreanum on the Proliferation and Differentiation of Primary Osteoblasts In Vitro - Jinchao Zhang; Yaping Li; Jing Sun; Cuilian Liu; Dawei Zhang (Biological Trace Element Research, 2011)

Identification and characterisation of candidate genes involved in chilling responses in maize (Zea mays L.) - Guang Yang; Hongda Zou; Ying Wu; Hongkui Liu; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Molecular characterization, polymorphism of bovine ZBTB38 gene and association with body measurement traits in native Chinese cattle breeds - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Linqiang Li; Wentao Cui; Zhonglin Tang; Kui Li (Molecular Biology Reports, 2010)

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)

Population genetic analysis of 6 Y-STR loci in Chinese northwestern Qinchuan yellow cattle breed - Yaping Xin; Linsen Zan; Yongfeng Liu; Hongyu Liu; Wanqiang Tian; Yueyuan Fan; Lei Huang (Molecular Biology Reports, 2010)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

Construction and Characterization of Two Bacterial Artificial Chromosome Libraries of Grass Carp - Songhun Jang; Hang Liu; Jianguo Su; Feng Dong; Feng Xiong; Lanjie Liao; Yaping Wang; Zuoyan Zhu (Marine Biotechnology, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

Distribution of borehole temperature at four high-altitude alpine glaciers in Central Asia - Yaping Liu; Shugui Hou; Yetang Wang; Linlin Song (Journal of Mountain Science, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Glacier extent and volume change (1966∼2000) on the Su-lo Mountain in northeastern Tibetan Plateau, China - Yetang Wang; Shugui Hou; Sungmin Hong; Soon Do Hur; Yaping Liu (Journal of Mountain Science, 2008)

Maternal cigarette smoking, metabolic gene polymorphisms, and preterm delivery: new insights on G×E interactions and pathogenic pathways - Hui-Ju Tsai; Xin Liu; Karen Mestan; Yunxian Yu; Shanchun Zhang; Yaping Fang; Colleen Pearson; Katherin Ortiz; Barry Zuckerman; Howard Bauchner; Sandra Cerda; Phillip G. Stubblefield; et al. (Human Genetics, 2008)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)

Sequence comparison of partial cytochrome b genes of two Coilia species - Jinxian Liu; Tianxiang Gao; Yujiang Wang; Yaping Zhang (Journal of Ocean University of China, 2005)

Toxicokinetic and genomic analysis of chronic arsenic exposure in multidrug-resistance mdr1a/1b(−/−) double knockout mice - Yaxiong Xie; Jie Liu; Yaping Liu; Curtis D. Klaassen; Michael P. Waalkes (Molecular and Cellular Biochemistry, 2004)

Increasing the transient expression of GUS gene in Porphyra yezoensis by 18S rDNA targeted homologous recombination - Hongquan Liu; Wengong Yu; Jixun Dai; Qianhong Gong; Kunfeng Yang; Yaping Zhang (Journal of Applied Phycology, 2003)